F-SiO2 Janus microsphere and super-hydrophobic coating based on F-SiO2 Janus microsphere

Clicked a chemical reactions on the surface of SiO2 nano-balls, picking 1h, 1h, 2H, 2H, 2H-whole fluorophytic acrylate, prepare F-SIO2JANUS microspheres with ultra-hydrophobic performance, and passed the hydroxyl acrocylite resin The cross -linking response forms a stable cross -linking network structure, solves the problem of poor durability of ultra -hydrophobic coating, and realizes the high durability and resistance of the coating.

CN119368110AActive Publication Date: 2025-01-28SHAANXI UNIV OF SCI & TECH

Patent Information

Application Number
CN202411744013.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-30
Publication Date
2025-01-28
Estimated Expiration
2044-11-30

AI Technical Summary

Technical Problem

The poor durability of existing superhydrophobic coatings is mainly due to insufficient adhesion between the coating and the substrate and the instability of the internal structure of the coating.

Method used

Adopt F-SIO2JANUS microspheres to prepare, and clicks chemical reactions on the surface of the SiO2 nano-ball ball, picking 1h, 1H, 2H, 2H-whole fluoropic fluoropic acrylate, forming an ultra-hydrophobic performance F-SIO2JANUS micro The ball also forms a stable cross -linking network structure through the cross -linking response to the hydroxyl acrylic resin.

Benefits of technology

It significantly improves the durability and resistance of ultra -hydrophobic coating, enhances the overall structural stability of the coating, and effectively suppresses the performance recession under long -term use or external friction.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

The invention discloses F-SiO2 Janus microspheres and a super-hydrophobic coating based on the F-SiO2 Janus microspheres, a preparation method of the F-SiO2 Janus microspheres comprises the following steps: adding SiO2 nanospheres and cetyltrimethylammonium bromide into a two-phase solvent of water and toluene, then adjusting the pH value of the system to 7-8, adding mercaptopropyltrimethoxysilane for reaction, and preparing mercaptopropyltrimethoxysilane modified SiO2 nanospheres; and adding a catalyst, 1H, 1H, 2H, 2H-perfluorodecyl acrylate and the mercaptopropyltrimethoxysilane modified SiO2 nanospheres into acetone, carrying out uniform ultrasonic dispersion, and in an ice bath environment, initiating a reaction through ultraviolet irradiation to prepare the F-SiO2 Janus microspheres. The F-SiO2 Janus microsphere prepared by the invention is used as a filler to be added into resin to form a coating, and the coating has good super-hydrophobic performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of functional coating development, and relates to F-SiO2Janus microspheres and a super-hydrophobic coating based thereon. Background Art

[0002] As a surface treatment technology with excellent waterproof, self-cleaning, anti-corrosion and anti-icing properties, super-hydrophobic coating has received extensive attention and application in many fields in recent years. However, despite its outstanding performance, the durability of super-hydrophobic coating has been a problem that has plagued researchers and users, becoming a key factor restricting its widespread application. The poor durability of super-hydrophobic coatings mainly stems from multiple aspects. First, the insufficient adhesion between the coating and the substrate is an important cause of coating failure. If the bonding between the coating and the substrate is not firm, it is easy to fall off or peel off under the action of external environmental factors. Secondly, the stability of the internal structure of the coating has an important influence on the durability of the coating. The stability of the internal structure of the coating is also affected by environmental factors such as temperature and humidity. These factors may cause uneven stress distribution inside the coating, which in turn causes the coating to crack or fall off. Therefore, optimizing the internal structure of the coating and improving the stability and corrosion resistance of the coating are important ways to improve the durability of super-hydrophobic coatings. In addition, most of the current super-hydrophobic materials are dispersed inside the matrix resin through physical action, and the bonding force with the resin is weak, affecting its durability. Summary of the invention

[0003] In view of the problems existing in the prior art, the present invention provides a F-SiO2Janus microsphere and a super hydrophobic coating based thereon, thereby solving the technical problem of poor durability of the super hydrophobic coating in the prior art.

[0004] The present invention is achieved through the following technical solutions: A method for preparing F-SiO2Janus microspheres comprises the following steps: S1: Add SiO2 nanospheres and hexadecyltrimethylammonium bromide into a two-phase solvent of water and toluene, then adjust the pH value of the system to 7-8, add mercaptopropyltrimethoxysilane for reaction, and obtain mercaptopropyltrimethoxysilane-modified SiO2 nanospheres; S2: Add the catalyst, 1H,1H,2H,2H-perfluorodecyl acrylate and the mercaptopropyltrimethoxysilane modified SiO2 nanospheres into acetone, disperse them uniformly by ultrasonication, and initiate the reaction by ultraviolet light in an ice bath environment to obtain the F-SiO2Janus microspheres.

[0005] Preferably, the ratio of the SiO2 nanospheres to mercaptopropyltrimethoxysilane is (0.5~3.0) g: (100~600) μL.

[0006] Preferably, the particle size of the SiO2 nanospheres is 30-500 nm.

[0007] Preferably, when adding mercaptopropyltrimethoxysilane for reaction, the reaction temperature is 85-95° C. and the reaction time is 1-6 h.

[0008] Preferably, the mass ratio of the 1H,1H,2H,2H-perfluorodecyl acrylate to the mercaptopropyltrimethoxysilane-modified SiO2 nanospheres is (0.1-0.35):(0.3-1.05).

[0009] Preferably, the reaction time of the ultraviolet light-induced reaction is 0.5 to 3 hours.

[0010] A F-SiO2 Janus microsphere is prepared by the above method.

[0011] A super-hydrophobic coating comprises a primer and a topcoat; the primer comprises the F-SiO2Janus microspheres and a hydroxy acrylic resin as described in claim 7; the topcoat comprises the F-SiO2Janus microspheres and a curing agent as described in claim 7.

[0012] Preferably, the content of F-SiO2Janus microspheres in the primer is 0.02-0.12 g / mL, and the content of F-SiO2Janus microspheres in the topcoat is 0.04-0.30 g / mL.

[0013] The above-mentioned super-hydrophobic coating is used in the preparation of a super-hydrophobic coating, firstly coating a primer on the surface of the substrate, and then coating a topcoat; the coating amount of the primer and the topcoat is 0.05~0.06mL / cm 2 ; The water contact angle of the super hydrophobic coating is 150°~154°, and the rolling angle is 4°~8°.

[0014] Compared with the prior art, the present invention has the following beneficial technical effects: The invention discloses a preparation method of F-SiO2Janus microspheres. In the preparation process, SiO2 nanospheres are uniformly dispersed at an organic-water two-phase interface, and then mercaptopropyl trimethoxysilane is added to the system, the mercaptopropyl trimethoxysilane is located in the water phase, and the mercaptopropyl trimethoxysilane modifies the surface of the SiO2 nanospheres in the water phase, and then 1H, 1H, 2H, 2H-perfluorodecyl acrylate is added in the presence of a catalyst, and under the action of ultraviolet light, the mercapto group on the mercaptopropyl trimethoxysilane and the double bond on the 1H, 1H, 2H, 2H-perfluorodecyl acrylate undergo a mercapto-ene click chemical reaction, thereby realizing super-hydrophobic modification of the surface of part of the SiO2 nanospheres. The material surface and the hydroxyl acrylic resin both have hydroxyl functional groups, and with the help of the isocyanate groups in the curing agent hexamethylene diisocyanate, the nanospheres and the hydroxyl acrylic resin form a stable cross-linked network structure through chemical bonding. This cross-linked network significantly improves the durability of the superhydrophobic coating. It not only enhances the overall structural stability of the coating, but also effectively inhibits the performance degradation of the coating under long-term use or external friction, thus giving it excellent durability and reliability.

[0015] Furthermore, the ratio of the SiO2 nanospheres to mercaptopropyltrimethoxysilane is (0.5~3.0) g:(100~600) μL. By adjusting the ratio of the two, the grafting rate of mercaptopropyltrimethoxysilane on the surface of the SiO2 nanospheres can be effectively controlled, thereby adjusting the number and distribution of reactive groups on the surface of the SiO2 nanospheres, providing a regulatory basis for subsequent functional modification.

[0016] Furthermore, the particle size of the SiO2 nanospheres is 30-500 nm. By regulating the particle size of the nanospheres, a coating with a differentiated micro-nano dual-scale rough structure can be provided, thereby adjusting the super-hydrophobic properties of the coating and further improving its functional properties.

[0017] Furthermore, when adding mercaptopropyltrimethoxysilane to the reaction, the reaction temperature is 85-95°C and the reaction time is 1-6h. By regulating the reaction conditions, the hydrolysis environment of mercaptopropyltrimethoxysilane can be effectively adjusted, thereby controlling the degree of grafting on the surface of SiO2 nanospheres. The change in the degree of grafting further affects the number and distribution of reactive groups on the surface of SiO2 nanospheres, providing a basis for subsequent functional modification.

[0018] Furthermore, the mass ratio of 1H,1H,2H,2H-perfluorodecyl acrylate to mercaptopropyltrimethoxysilane modified SiO2 nanospheres is (0.1~0.35):(0.3~1.05), which can be regulated to optimize the performance of the obtained F-SiO2Janus nanospheres, significantly improving the superhydrophobic properties of the coating, including a higher water contact angle and a lower rolling angle, thereby enhancing the water resistance and durability of the coating.

[0019] Furthermore, the ultraviolet light-induced reaction time is 0.5 to 3 h, which can effectively promote the full progress of the thiol-ene click chemistry reaction, thereby significantly improving the grafting efficiency of 1H, 1H, 2H, 2H-perfluorodecyl acrylate on the surface of the microspheres, enhancing the degree of surface functionalization, and providing a reliable material for the excellent superhydrophobic properties of the coating.

[0020] In addition, the present invention also discloses a super-hydrophobic coating, including a primer and a topcoat; the primer includes the above-mentioned F-SiO2Janus microspheres and a hydroxy acrylic resin; the topcoat includes the above-mentioned F-SiO2Janus microspheres and a curing agent.

[0021] Furthermore, the content of F-SiO2Janus microspheres in the primer is 0.02~0.12g / mL, and the content of F-SiO2Janus microspheres in the topcoat is 0.04~0.30g / mL. By adjusting the mass ratio, the performance of the obtained F-SiO2Janus nanospheres can be optimized, and the superhydrophobic properties of the coating are significantly improved, including a higher water contact angle and a lower rolling angle, thereby enhancing the water resistance and durability of the coating.

[0022] At the same time, the present invention also discloses the use of the above-mentioned super-hydrophobic coating in the preparation of a super-hydrophobic coating, firstly coating a primer on the surface of a substrate, and then coating a topcoat; the coating amounts of the primer and the topcoat are both 0.05-0.06 mL / cm 2 By adjusting the coating amount, the cross-linking effect of F-SiO2Janus nanospheres in the coating can be effectively improved, thereby giving the super-hydrophobic coating excellent durability, manifested as higher wear resistance and long-term waterproof performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments are briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.

[0024] Figure 1 This is a transmission electron microscope image of silver-labeled F-SiO2Janus microspheres; Figure 2 This is a photo of F-SiO2Janus microspheres stabilized emulsion; Figure 3 This is a photo of the liquid contact angle of the superhydrophobic coating; Figure 4 These are the test results of water contact angle and rolling contact angle of the super-hydrophobic coating constructed based on F-SiO2Janus microspheres prepared in Example 5 of the present invention after different cyclic friction experiments. DETAILED DESCRIPTION

[0025] In order to enable those skilled in the art to understand the characteristics and effects of the present invention, the following is a general description and definition of the terms and expressions mentioned in the specification and claims. Unless otherwise specified, all technical and scientific terms used in the text are the common meanings understood by those skilled in the art for the present invention. In the event of a conflict, the definition in this specification shall prevail.

[0026] The theories or mechanisms described and disclosed herein, whether correct or incorrect, should not limit the scope of the present invention in any way, that is, the present invention can be implemented without being limited by any specific theory or mechanism.

[0027] In this article, all features such as values, quantities, contents and concentrations defined in the form of numerical ranges or percentage ranges are for simplicity and convenience only. Accordingly, the description of numerical ranges or percentage ranges should be considered to have included and specifically disclosed all possible secondary ranges and individual values ​​within the range (including integers and fractions).

[0028] In this document, unless otherwise specified, “includes,” “including,” “contains,” “has,” or similar terms cover the meanings of “consisting of” and “mainly consisting of,” for example, “A includes a” covers the meanings of “A includes a and other” and “A only includes a.”

[0029] In this document, in order to make the description concise, not all possible combinations of various technical features in various embodiments or examples are described. Therefore, as long as there is no contradiction in the combination of these technical features, the various technical features in various embodiments or examples can be combined arbitrarily, and all possible combinations should be considered to be within the scope of this specification.

[0030] The present invention provides a method for preparing F-SiO2Janus microspheres, comprising the following steps: S1: Add SiO2 nanospheres and hexadecyltrimethylammonium bromide to a two-phase solvent of water and toluene, then add ammonia water, stir at 20-40°C for 20-40 minutes, adjust the pH value of the system to 7-8, add mercaptopropyltrimethoxysilane, react at 85-95°C for 1-6 hours, and obtain mercaptopropyltrimethoxysilane-modified SiO2 nanospheres; Wherein, the SiO2 nanospheres are solid nanospheres with a particle size of 30 to 500 nm.

[0031] The ratio of the SiO2 nanospheres to mercaptopropyltrimethoxysilane is (0.5-3.0) g: (100-600) μL.

[0032] Further preferably, the feed ratio of the SiO2 nanospheres, water, toluene, hexadecyltrimethylammonium bromide and mercaptopropyltrimethoxysilane is (0.50-3.00) g: (50-300) mL: (10-60) mL: (0.31-1.86) g: (100-600) μL; More preferably, the feed ratio of the SiO2 nanospheres, water, toluene, hexadecyltrimethylammonium bromide and mercaptopropyltrimethoxysilane is (0.50-2.5) g: (50-250) mL: (10-50) mL: (0.31-1.55) g: (100-500) μL; The preparation method of SiO2 nanospheres in the present invention is as follows: 10 mL of ammonia water, 50-250 mL of anhydrous ethanol and 30 mL of deionized water are added to a three-necked flask equipped with a digital display stirrer, and after stirring evenly for 20 minutes at 30°C, 10 mL of ethyl orthosilicate is added, and the reaction is continued for 5 hours. After the reaction is completed, SiO2 nanospheres with a particle size of 30-500 nm are obtained through centrifugation, washing and drying steps.

[0033] S2: Add the catalyst, 1H,1H,2H,2H-perfluorodecyl acrylate and the mercaptopropyltrimethoxysilane modified SiO2 nanospheres into acetone, disperse them evenly by ultrasonication, induce the mercapto-ene click reaction by ultraviolet light in an ice bath environment, and irradiate with light for 0.5 to 3 hours to obtain the F-SiO2Janus microspheres.

[0034] The above catalyst is benzoin dimethyl ether; The mass ratio of the 1H,1H,2H,2H-perfluorodecyl acrylate to the mercaptopropyltrimethoxysilane-modified SiO2 nanospheres is (0.1-0.35):(0.3-1.05).

[0035] Further preferably, the mass ratio of the catalyst, 1H,1H,2H,2H-perfluorodecyl acrylate and mercaptopropyltrimethoxysilane modified SiO2 nanospheres is (0.048~0.168):(0.1~0.35):(0.3~1.05).

[0036] The ratio of the 1H,1H,2H,2H-perfluorodecyl acrylate to acetone is (0.3-1.05) g: (60-210) mL.

[0037] During the above ultraviolet irradiation process, the wavelength of the ultraviolet light is 365nm.

[0038] The invention also discloses a F-SiO2 Janus microsphere prepared by the method.

[0039] In addition, the present invention also discloses a super hydrophobic coating, including a primer and a topcoat; the primer includes the above-mentioned one kind of F-SiO2Janus microspheres and hydroxy acrylic resin, and the solvent is ethyl acetate; the topcoat includes the above-mentioned one kind of F-SiO2Janus microspheres and a curing agent, and the solvent is ethyl acetate. The curing agent is preferably hexamethylene diisocyanate.

[0040] Preferably, the solid content of the primer is 0.1-0.6 g / mL, the content of F-SiO2Janus microspheres in the primer is 0.02-0.12 g / mL, the solid content of the topcoat is 0.05-0.35 g / mL, and the content of F-SiO2Janus microspheres in the topcoat is 0.04-0.30 g / mL.

[0041] At the same time, the present invention also discloses the use of the above-mentioned super-hydrophobic coating in the preparation of a super-hydrophobic coating. First, a primer is applied to the surface of a substrate, and then a topcoat is applied. After drying, a super-hydrophobic coating is obtained.

[0042] The coating amount of the primer and topcoat is 0.05-0.06 mL / cm 2 ; The water contact angle of the super hydrophobic coating is 150°~154°, and the rolling angle is 4°~8°.

[0043] The invention discloses a F-SiO2Janus microsphere, which retains the original hydroxyl group at one end of the surface of the SiO2 nanosphere and grafts a hydrophilic thiol group at the other end, has a significant asymmetric structure, and then grafts 1H, 1H, 2H, 2H-perfluorodecyl acrylate on the surface to provide a hydrophobic segment. The preparation method of the F-SiO2Janus microsphere uses the reactive group double bond of the hydrophilic segment and the reactive group thiol of one segment of the SH-SiO2Janus microsphere modified with mercaptopropyltrimethoxysilane in an acetone solution through a mercaptoene click chemical reaction under the reactivity of mercaptoene-click chemistry to obtain the F-SiO2Janus microsphere. The present invention utilizes F-SiO2Janus microspheres to make them directional on the coating surface, with the inorganic end facing the hydroxyl acrylate coating on the coating surface, and the organic lyophobic segment facing the air, and the micro-nano rough structure constructed by the F-SiO2Janus microspheres and the low surface energy material provided by the organic lyophobic segment are used to realize the super-hydrophobic performance of the coating, and in addition, the reactive group hydroxyl group of the inorganic end and the isocyanate group on the molecular chain of the hydroxyl acrylate crosslinking agent hexamethylene diisocyanate produce chemical crosslinking to improve the durability of the coating. The super-hydrophobic coating prepared by the F-SiO2Janus microspheres of the present invention has a water contact angle of 152°±1.5° and a rolling angle of 6°±1.8°.

[0044] The present invention discloses a preparation method and application of a super-hydrophobic coating based on F-SiO2Janus microspheres, and belongs to the field of nano-functional materials. The preparation method of F-SiO2Janus microspheres comprises: (1) using silica nanospheres as carriers, and using silane coupling agents to perform unilateral modification to prepare modified silica nanospheres; (2) through click chemistry reaction, grafting hydrophobic segments onto the modified Janus microspheres to obtain F-SiO2Janus microspheres with super-hydrophobic function; further, using the F-SiO2Janus microspheres to prepare super-hydrophobic coatings, the microspheres have excellent performance and strong adaptability; (4) the prepared F-SiO2Janus microspheres can undergo cross-linking reaction with hydroxy acrylic resin, and the resin can be applied to a variety of substrates such as glass, wood, PMMA board and steel. The super-hydrophobic coating of the present invention has a wide range of application value in the fields of waterproofing and anti-fouling.

[0045] The present invention will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. In addition, it should be understood that after reading the content taught by the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms fall within the scope limited by the appended claims of the application equally.

[0046] The following examples use conventional instruments and equipment in the art. The experimental methods in the following examples where specific conditions are not specified are usually carried out under conventional conditions or under conditions recommended by the manufacturer. The various raw materials used in the following examples are conventional commercial products unless otherwise specified, and their specifications are conventional specifications in the art. In the specification of the present invention and the following examples, unless otherwise specified, "%" means weight percentage, "part" means weight part, and ratio means weight ratio.

[0047] Example 1 A method for preparing F-SiO2Janus microspheres, comprising the following steps Step 1, 0.50g SiO2 nanospheres with a particle size of 30nm, 0.31g hexadecyltrimethylammonium bromide, 50mL deionized water, and 10mL toluene are mixed, and ultrasonic treatment is carried out at 20°C for 20min, and then 1.5mL deionized water and 1.5mL ammonia water are added and the temperature is raised to 85°C for treatment for 1h, and then 100μL mercaptopropyltrimethoxysilane is added and the reaction is kept at 85°C for 1h, and then washed with toluene, ethanol, and deionized water in turn, and dried to obtain mercaptopropyltrimethoxysilane-modified SiO2 nanospheres.

[0048] Step 2, after mixing 0.048 g of benzoin dimethyl ether, 0.1 g of 1H,1H,2H,2H-perfluorodecyl acrylate, 0.3 g of mercaptopropyltrimethoxysilane-modified SiO2 nanospheres and 60 mL of acetone, irradiate with ultraviolet light for 0.5 h in an ice bath, and wash by centrifugation with ethanol to obtain F-SiO2Janus microspheres.

[0049] The super hydrophobic coating is prepared based on the above-mentioned F-SiO2Janus microspheres, and the preparation method thereof is as follows: First, apply 0.1g / mL primer on the substrate surface with a spraying amount of 0.05mL / cm 2 Then apply 0.05g / mL topcoat with a spray volume of 0.05mL / cm 2 , and after drying, a super-hydrophobic coating was obtained.

[0050] Example 2 A method for preparing F-SiO2Janus microspheres, comprising the following steps Step 1, 1.00g SiO2 nanospheres with a particle size of 120nm, 0.62g hexadecyltrimethylammonium bromide, 100mL deionized water, and 20mL toluene are mixed, and ultrasonic treatment is carried out at 24°C for 24min, and then 3mL deionized water and 3mL ammonia water are added and the temperature is raised to 87°C. After treatment for 2h, 200μL mercaptopropyltrimethoxysilane is added, and the reaction is kept at 87°C for 2h, and then washed with toluene, ethanol, and deionized water in turn, and dried to obtain mercaptopropyltrimethoxysilane-modified SiO2Janus microspheres.

[0051] Step 2, after mixing 0.068 g of benzoin dimethyl ether, 0.14 g of 1H,1H,2H,2H-perfluorodecyl acrylate, 0.45 g of mercaptopropyltrimethoxysilane-modified SiO2Janus microspheres and 90 mL of acetone, irradiate with ultraviolet light for 1 h in an ice bath, and wash by centrifugation with ethanol to obtain F-SiO2Janus microspheres.

[0052] A superhydrophobic coating was prepared based on the above-mentioned F-SiO2Janus microspheres.

[0053] Its preparation method is: First, apply 0.6g / mL primer on the substrate surface with a spraying amount of 0.06mL / cm 2 Then apply 0.35g / mL topcoat with a spray volume of 0.06mL / cm 2 , and after drying, a super-hydrophobic coating was obtained.

[0054] Example 3 A method for preparing F-SiO2Janus microspheres, comprising the following steps Step 1, 1.5g SiO2 nanospheres with a particle size of 210nm, 0.93g hexadecyltrimethylammonium bromide, 150mL deionized water, and 30mL toluene are mixed, and ultrasonic treatment is carried out at 28°C for 28min, and then 4.5mL deionized water and 4.5mL ammonia water are added, and the temperature is raised to 89°C and treated for 3h, and then 300μL of mercaptopropyltrimethoxysilane is added, and the reaction is carried out at 87°C for 3h, and then the mixture is washed with toluene, ethanol, and deionized water in turn, and dried to obtain mercaptopropyltrimethoxysilane-modified SiO2 nanospheres.

[0055] Step 2, after mixing 0.088 g of benzoin dimethyl ether, 0.18 g of 1H,1H,2H,2H-perfluorodecyl acrylate, 0.6 g of mercaptopropyltrimethoxysilane-modified SiO2 nanospheres and 120 mL of acetone, irradiate with ultraviolet light for 1.5 h in an ice bath, and wash by centrifugation with ethanol to obtain F-SiO2Janus microspheres.

[0056] The super hydrophobic coating is prepared based on the above-mentioned F-SiO2Janus microspheres, and the preparation method thereof is as follows: First, apply 0.2g / mL primer on the substrate surface with a spraying amount of 0.05mL / cm 2 Then apply 0.15g / mL topcoat with a spray volume of 0.05mL / cm 2 , and after drying, a super-hydrophobic coating was obtained.

[0057] Example 4 A method for preparing F-SiO2Janus microspheres, comprising the following steps Step 1, 2.00g SiO2 nanospheres with a particle size of 300nm, 1.24g hexadecyltrimethylammonium bromide, 200mL deionized water, and 40mL toluene are mixed, and then ultrasonically dispersed, and ultrasonically treated at 32°C for 32min, and then 6mL deionized water and 6mL ammonia water are added, and treated at 91°C for 4h, and then 400μL mercaptopropyltrimethoxysilane is added, and the reaction is carried out at 91°C for 4h, and then washed with toluene, ethanol, and deionized water in turn, and dried to obtain mercaptopropyltrimethoxysilane-modified SiO2 nanospheres.

[0058] Step 2, 0.108 g of benzoin dimethyl ether, 0.24 g of 1H,1H,2H,2H-perfluorodecyl acrylate, 0.75 g of mercaptopropyltrimethoxysilane-modified SiO2 nanospheres and 150 mL of acetone were mixed, and then irradiated with ultraviolet light for 2 h in an ice bath, and washed by centrifugation with ethanol to obtain F-SiO2Janus microspheres.

[0059] The super hydrophobic coating is prepared based on the above-mentioned F-SiO2Janus microspheres, and the preparation method thereof is as follows: First, apply 0.5g / mL primer on the substrate surface with a spraying amount of 0.06mL / cm 2 Then apply 0.30g / mL topcoat with a spray volume of 0.05mL / cm 2 , and after drying, a super-hydrophobic coating was obtained.

[0060] Example 5 A method for preparing F-SiO2Janus microspheres, comprising the following steps Step 1, 2.5g SiO2 nanospheres with a particle size of 400nm, 1.53g hexadecyltrimethylammonium bromide, 250mL deionized water, and 50mL toluene are mixed, and ultrasonic treatment is carried out at 36°C for 36min, and then 7.5mL deionized water and 7.5mL ammonia water are added, and the mixture is treated at 93°C for 5h, and then 500μL mercaptopropyltrimethoxysilane is added, and the mixture is reacted at 93°C for 5h, and the mixture is washed with toluene, ethanol, and deionized water in sequence, and dried to obtain mercaptopropyltrimethoxysilane-modified SiO2 nanospheres.

[0061] Step 2, 0.138 g of benzoin dimethyl ether, 0.3 g of 1H,1H,2H,2H-perfluorodecyl acrylate, 0.9 g of mercaptopropyltrimethoxysilane-modified SiO2 nanospheres and 180 mL of acetone were mixed, and then irradiated with ultraviolet light for 2.5 h in an ice bath, and washed by centrifugation with ethanol to obtain F-SiO2Janus microspheres.

[0062] The super hydrophobic coating is prepared based on the above-mentioned F-SiO2Janus microspheres, and the preparation method thereof is as follows: First, apply 0.3g / mL primer on the substrate surface with a spraying amount of 0.05mL / cm2 Then apply 0.2g / mL topcoat with a spray volume of 0.05mL / cm 2 , and after drying, a super-hydrophobic coating was obtained.

[0063] Example 6 A method for preparing F-SiO2Janus microspheres, comprising the following steps Step 1, 3.00g SiO2 nanospheres with a particle size of 500nm, 1.86g hexadecyltrimethylammonium bromide, 300mL deionized water, and 60mL toluene are mixed, ultrasonically treated at 40°C for 40min, 9mL deionized water and 9mL ammonia water are added, treated at 95°C for 6h, 600μL mercaptopropyltrimethoxysilane is added, reacted at 95°C for 6h, washed with toluene, ethanol, and deionized water in turn, and dried to obtain mercaptopropyltrimethoxysilane-modified SiO2 nanospheres.

[0064] Step 2, 0.168 g of benzoin dimethyl ether, 0.35 g of 1H,1H,2H,2H-perfluorodecyl acrylate, 1.05 g of mercaptopropyltrimethoxysilane-modified SiO2 nanospheres and 210 mL of acetone were mixed, and then irradiated with ultraviolet light for 3 h in an ice bath, and washed by centrifugation with ethanol to obtain F-SiO2Janus microspheres.

[0065] The super hydrophobic coating is prepared based on the above-mentioned F-SiO2Janus microspheres, and the preparation method thereof is as follows: First, apply 0.4g / mL primer on the substrate surface with a spraying amount of 0.055mL / cm 2 Then apply 0.25g / mL topcoat with a spray volume of 0.055mL / cm 2 , and after drying, a super-hydrophobic coating was obtained.

[0066] The morphology of the F-SiO2Janus microspheres prepared in Example 5 of the present invention was characterized, and the TEM test results are as follows: Figure 1 As shown. Figure 1 It can be seen that part of the surface of the F-SiO2Janus microspheres contains covered 1H,1H,2H,2H-perfluorodecyl acrylate, while the other part does not, with a significant asymmetric structure, indicating that the F-SiO2Janus microspheres were successfully prepared using this method.

[0067] Figure 2 This is an optical microscope photo of the F-SiO2Janus microsphere stabilized emulsion. The F-SiO2Janus microspheres were added to a mixed emulsion of dodecane and dimethyl sulfoxide, and ultrasonic cell crushing and emulsification were performed for ten minutes. The emulsion was placed under an upright microscope, and its stable emulsion droplets can be observed, indicating that it has amphiphilicity.

[0068] Figure 3 The liquid contact angle photo of the super-amphiphobic coating prepared in Example 5 is shown in FIG. Figure 3 It can be seen that the water contact angle of the super hydrophobic coating prepared by the present invention reaches 153°±1.7° and the rolling angle is 5°±2.1°, which has excellent super hydrophobic properties.

[0069] Figure 4 The water contact angle and rolling contact angle test results of the super-amphiphobic coating constructed based on F-SiO2Janus microspheres prepared in Example 5 of the present invention after different cyclic friction experiments, as shown in the figure, as shown in the figure, when not rubbed, the super-amphiphobic coating shows excellent super-hydrophobic performance, and its water contact angle and rolling angle are 158.9 ± 0.9 ° and 1.7 ± 0.6 ° respectively. With the increase of the number of frictions, the water contact angle of the coating gradually decreases, and the rolling angle gradually increases. After 70 friction cycles, the water contact angle and rolling angle of the coating are 150. ± 0.9 ° and 8.9 ± 0.7 ° respectively, indicating that the coating still possesses significant super-hydrophobic ability. The superiority of this wear resistance is due to the chemical crosslinking and physical bonding between F-SiO2Janus microspheres and hydroxy acrylic resin, which effectively suppresses the shedding of nanospheres during friction, thereby ensuring the micro-nano structure stability of the coating surface, and significantly improving its wear-resistant super-hydrophobic performance.

[0070] In summary, the present invention successfully prepared F-SiO2Janus microspheres, and then through layer-by-layer spraying, the hydrophilic end was chemically cross-linked with the substrate to obtain a super-hydrophobic coating.

[0071] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.

Claims

1. A method for preparing F-SiO2 Janus microspheres, characterized in that: The following steps are involved: S1: Add SiO2 nanospheres and hexadecyltrimethylammonium bromide into a two-phase solvent of water and toluene, then adjust the pH value of the system to 7-8, add mercaptopropyltrimethoxysilane for reaction, and obtain mercaptopropyltrimethoxysilane-modified SiO2 nanospheres; S2: Add the catalyst, 1H,1H,2H,2H-perfluorodecyl acrylate and the mercaptopropyltrimethoxysilane modified SiO2 nanospheres into acetone, disperse them uniformly by ultrasonication, and initiate the reaction by ultraviolet light in an ice bath environment to obtain the F-SiO2 Janus microspheres.

2. The method for preparing F-SiO2 Janus microspheres according to claim 1, characterized in that: The ratio of the SiO2 nanospheres to mercaptopropyltrimethoxysilane is (0.5-3.0) g: (100-600) μL.

3. The method for preparing F-SiO2 Janus microspheres according to claim 1, characterized in that: The particle size of the SiO2 nanospheres is 30-500 nm.

4. The method for preparing F-SiO2 Janus microspheres according to claim 1, characterized in that: When adding mercaptopropyltrimethoxysilane for reaction, the reaction temperature is 85-95° C. and the reaction time is 1-6 hours.

5. The method for preparing F-SiO2 Janus microspheres according to claim 1, characterized in that: The mass ratio of the 1H,1H,2H,2H-perfluorodecyl acrylate to the mercaptopropyltrimethoxysilane-modified SiO2 nanospheres is (0.1-0.35):(0.3-1.05).

6. The method for preparing F-SiO2 Janus microspheres according to claim 1, characterized in that: The reaction time of the ultraviolet light-induced reaction is 0.5 to 3 hours.

7. A F-SiO2 Janus microsphere, characterized in that: Prepared by the method according to any one of claims 1 to 6.

8. A super hydrophobic coating, characterized in that, It comprises a primer and a topcoat; the primer comprises the F-SiO2 Janus microspheres as claimed in claim 7 and a hydroxy acrylic resin; the topcoat comprises the F-SiO2 Janus microspheres as claimed in claim 7 and a curing agent.

9. A super hydrophobic coating according to claim 8, characterised in that The content of F-SiO2 Janus microspheres in the primer is 0.02-0.12 g / mL, and the content of F-SiO2 Janus microspheres in the topcoat is 0.04-0.30 g / mL.

10. The use of a super-hydrophobic coating according to any one of claims 8 to 9 in the preparation of a super-hydrophobic coating, characterized in that First, a primer is applied to the surface of the substrate, and then a topcoat is applied; the coating amount of the primer and the topcoat is 0.05-0.06 mL / cm 2 ; The water contact angle of the super hydrophobic coating is 150°~154°, and the rolling angle is 4°~8°.

Citation Information

Patent Citations

  • Janus type porous silicon dioxide compound nanoparticle and preparing method thereof

    CN110104654A

  • Super-hydrophobic nano silicon dioxide and preparation method thereof

    CN117843006A

Cited By

  • Preparation method of super-hydrophobic coating with multistage micro-nano structure

    CN120900926A

  • Mesoporous silicon-based Janus microsphere and preparation method thereof

    CN121672541A